Food losses perceived by family farms: Challenges and policy implications from a micro-approach quantification - Herrera-Quinteros, Gabriela; Jara-Rojas, Roberto (Frontiers in Sustainable Food Systems, 2023)
During the last decade, food loss and waste (FLW) has been gaining more attention due to its negative effect on food security. However, the lack of information about FLW quantification and characterization remains a problem, especially from the perspectives of local citizens and farmers. There is limited literature examining food losses (FL) in primary production of the food supply chain (FSC) and specific policies are needed to improve the FLW measurement. The aim of this research is to analyze how much FL is generated at the farm level using a micro approach methodology from harvest to primary commercialization stages among farmers located in Central Chile. Additionally, we explore factors affecting FL using a fractional regression model with special emphasis on the harvest stage. Data was collected using phone interviews, conducted in 2019, to 177 small-scale producers of vegetables and berries. FL generated by the sample from harvest to primary commercialization was 14.5% on average. Farmers identified a considerable volume of FL during primary production, mostly during the harvest. The factors that increased FL among small-scale farmers were the production system and its harvest period, commercialization channels, labor shortage, and cosmetic standards. As a case study, the information collected here can be useful for encouraging further research emphasizing the harvest stage and role of the production systems in generating FLW.